What’s used and what’s useful? Exploring digital technology use(s) among taught postgraduate students - Henderson, Michael; Finger, Glenn; Selwyn, Neil (Active learning in higher education, 2016)
This article explores the digital technologies that taught postgraduate students engage with during their studies, what these technologies are used for and how useful they are perceived to be. The article draws upon data gathered from a survey of 253 masters and postgraduate diploma/certificate students across two universities in Australia. Analysis of these data contrasts the varied use(fulness) of ‘official’ university technologies such as learning management systems and library resources against ‘unofficial’ technologies such as Wikipedia, Twitter, Facebook and free/open education resources. In particular, the data highlight notable differences between students by subject area, domicile, mode of study and academic performance. The data also highlight the perceived benefits of this technology use – with students primarily finding digital technology useful in terms of supporting the logistics of university study rather than matters of learning per se. The article concludes by considering what is missing from these current forms of technological engagement, particularly in comparison with wider discourses about the educational potential of recent digital technologies.